2020
DOI: 10.1111/ina.12656
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and pro‐inflammatory potential of indoor mold particles

Abstract: A number of epidemiological studies find an association between indoor air dampness and respiratory health effects. This is often suggested to be linked to enhanced mold growth. However, the role of mold is obviously difficult to disentangle from other dampness‐related exposure including microbes as well as non‐biological particles and chemical pollutants. The association may partly be due to visible mycelial growth and a characteristic musty smell of mold. Thus, the potential role of mold exposure should be f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 246 publications
(579 reference statements)
0
8
0
1
Order By: Relevance
“…Chemical assays cannot determine the harmfulness of total exposure to microbial and anthropogenic toxins or their interactions. Thus, bioassays providing an integrated picture of overall toxicity are essential tools for understanding toxic mechanisms, detecting known and unknown toxins, and studying the potential health relevance of complex toxic exposure [37,[57][58][59][60]. However, sensitivity and specificity varies in different bioassays, and there is no single comprehensive method for detecting all potentially adverse effects of indoor air on human health.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical assays cannot determine the harmfulness of total exposure to microbial and anthropogenic toxins or their interactions. Thus, bioassays providing an integrated picture of overall toxicity are essential tools for understanding toxic mechanisms, detecting known and unknown toxins, and studying the potential health relevance of complex toxic exposure [37,[57][58][59][60]. However, sensitivity and specificity varies in different bioassays, and there is no single comprehensive method for detecting all potentially adverse effects of indoor air on human health.…”
Section: Discussionmentioning
confidence: 99%
“…The components of DM may specifically destroy the function of the cilia cells of the epithelium. Thus, the barrier function of mucosal layer of bronchi may be impaired and inhaled impurities may not be removed properly [1,8]. This dysfunction of the innate immunity paves the way for better pathogen entry.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…shown that spores and hyphal fragments are liberated from natural occurring mould cultures and became airborne. 831 It was shown that particular mould allergens, Asp f 1 832 and Alt a 1 were detected in spores. 833,834 But other allergens like Alt a 8, a mannitol dehydrogenase, were exclusively localized in vacuole-like compartments of the hyphae.…”
Section: -The Sourcementioning
confidence: 99%